Analysis of clinical and pathological prognostic factors of survival in rectal adenocarcinoma treated with preoperative radiochemotherapy - Sarhan Sydney Saad; Nora Forones; Gaspar Lopes Filho; Jaques Waisberg; Elesiario Caetano Júnior; Ricardo Artigiani-Neto; Delcio Matos (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To identify the prognostic variables related to the survival of patients operated on for adenocarcinoma of the rectum who underwent preoperative radiochemotherapy (RCT). Methods: We studied 70 patients from the Discipline of Surgical Gastroenterology at Escola Paulista de Medicina from 2000 to 2019, with rectal cancer located up to 10 cm from the anal verge and with stages II or III, submitted to preoperative RCT and curative surgery (R0) and with follow-up of at least 12 months. Clinical restaging was performed four to six weeks after the end of neoadjuvant treatment to characterize the degree of clinical tumor regression. Surgery by laparotomy or videolaparoscopy was performed six to 12 weeks after RCT. Primary endpoint were: overall survival (OS), disease-free survival (DFS), metastasis-free survival (MSS), and neoplasm-specific survival (SEN). These were compared with gender, age, carcinoembryonic antigen (CEA) dosage, distance from the tumor to the anal verge, radiation dose, radiotherapy-surgery interval, clinical regression, type of surgery, pT and pN TNM stage tumor, number of nodes, circumferential resection margin, and complete pathological response. Survival was assessed by Kaplan-Meier curves. Univariate and multivariate Cox analyses were calculated to identify factors associated with survival outcomes. Results: The mean follow-up time was 62 months. The pathological complete response rate was 18.6%. Univariate cox regression showed a significant relationship of CEA equal to or greater than 4 ng/mL with DFS and MFS, pT3/pT4 staging with DFS, MFS and SEN, pN1/N2 with DFS, MFS and SEN and stages II and III with DFS and MFS. Multivariate regression found that CEA, pT, and pN staging are independent prognostic factors for DFS, MFS, and SEN. Conclusion: Carcinoembryonic antigen level prior to radiotherapy, pT staging and pN staging were independent prognostic factors for survival in patients with rectal adenocarcinoma who are treated with preoperative radiochemotherapy.